2019
DOI: 10.1111/jfbc.12765
|View full text |Cite
|
Sign up to set email alerts
|

Structure-informed separation of bioactive peptides

Abstract: The application of proteomic and peptidomic technologies for food-derived bioactive peptides is an emerging field in food sciences. These technologies include the use of separation tools coupled to a high-resolution spectrometric and bioinformatic tools for prediction, identification, sequencing, and characterization of peptides. To a large extent, one-dimensional separation technologies have been extensively used as a continuous tool under different optimized conditions for the identification and analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 75 publications
(77 reference statements)
0
26
0
1
Order By: Relevance
“…The height and number of peaks also varied in the hydrophobic region (70-80 min) of the two chromatograms. The early peaks in chromatograms are mostly included low molecular weight hydrophilic peptides and amino acids and the peaks that appear later consist of hydrophobic peptides (Acquah et al, 2019). Differences between the two chromatograms showed that M8 was active on secondary proteolysis and the production of low molecular weight hydrophobic and hydrophilic peptides and amino acids in UF white cheese.…”
Section: Rp-hplc Peptide Profilementioning
confidence: 98%
“…The height and number of peaks also varied in the hydrophobic region (70-80 min) of the two chromatograms. The early peaks in chromatograms are mostly included low molecular weight hydrophilic peptides and amino acids and the peaks that appear later consist of hydrophobic peptides (Acquah et al, 2019). Differences between the two chromatograms showed that M8 was active on secondary proteolysis and the production of low molecular weight hydrophobic and hydrophilic peptides and amino acids in UF white cheese.…”
Section: Rp-hplc Peptide Profilementioning
confidence: 98%
“…Those peptides which offer low hydrophobicity as well as a low molecular weight will usually exhibit a low retention time in the column as a result of their amino acid sequence, and will be the rst to be eluted. 34,35 RP-HPLC was used to separate the MW < 0.65 kDa fraction from the SPH which had been shown to offer the greatest antioxidant activity. A sample solution was prepared which encompassed molecular polarity differences.…”
Section: Free Radical Scavenging Activity Following Sph Size Fractionmentioning
confidence: 99%
“…In general, the peptide mixture is subjected to ultrafiltration at a given molecular weight cut-off and the peptides of interest are extracted or captured using immobilized metal affinity chromatography (IMAC). IMAC is the most widely used technique for isolating metal-binding peptides due to its high sensitivity, selectivity, binding capacity and recovery rate [ 18 , 42 ]. Thus, proteins and peptides that form specific reversible complexes with the metal ions of interest are separated by retention in the solid phase of the column as they are non-covalently linked to the metal [ 18 ].…”
Section: Preparation Purification and Identification Of Mineral-mentioning
confidence: 99%